A violência é a regra: um estudo jusliterário sobre as representações da Exceção em Rubião e Fonseca - MORENO, Priscila Karina Santos (2021)
The aesthetic and ethical project of many Brazilian writers is dedicated to revealing a crisis in today's society, of an existential, sociocultural and political nature. In this way, the writer offers an overview of social and humanitarian problems that transform the space of the literary composition in a camp of survival. In dialogue with the theory of the State of Exception and with the concept of naked life, by the philosopher Giorgio Agamben, the short stories Button of Rose (1974), by Murilo Rubião and Book of Occurrences (1979), by Rubem Fonseca, seem to be investing in the idea of the State of Exception of Right, first proclaimed by Walter Benjamin (1985-1986) and taken up as a construction of the Agambenian theory in later works. The objective is to understand, through the jusliterary bias, the current moment that contemporary democracies are going through, exposing how the logics of oppression of sovereign structures find their legitimacy in the rules of Law itself, and verify, through the fictional text, how the violence and the ideology of power over life are admitted - or at least tolerated - in the development of the actions of the examined plots. We start from the understanding that Literature has a subversive function of denouncing the status quo, when the fictional narrative allows the reflection of the social reality where it was produced. In order to achieve the established objective, it is necessary to consider the concepts of biopolitic, biopower and camp, presented by Foucault and Hannah Arendt, as well as the bevy, naked life, homo sacer (sacratio) and Exception, coined by Giorgio Agamben, in addition to the concept of Exception of Right, presented by Benjamim. For the critical-literary analysis of the thesis, we will use, in addition to other literary critics, some studies of the modern Brazilian short stories, the dialectical theory of Antonio Candido and the understandings of Alfredo Bosi and Benôit Denis about engaged literature and resistance literatura. The methodology used will be a bibliographic review, with a qualitative approach and exploratory character. The analyze short stories were chosen considering three aspects: their aesthetic value; the theme involved in it; and, as a consequence, the objects of the represented world.